Penerapan Media Gambar dalam Upaya Meningkatkan Hasil Belajar IPA Materi Bagian-Bagian Tumbuhan dan Fungsinya pada Siswa Kelas IVB SDK 077 Kecamatan Kewapante Kabupaten Sikka Tahun 2021/2022 - Non Monika Ketuko; Maria Helvina; Maria Herliyani Dua Bunga (Departement of Mathematics Education, 2023)
This study aims to find out the results of learning science for grade IV students through the Application of Media Pictures in an Effort to Improve Science Learning Outcomes on the Material of Plant Parts and Their Functions in Grade IVB Students SDK 007 Kewapante, Kewapante District, Sikka Regency, Academic Year 2021/2022. The type of research used in this research is classroom action research (CAR) with a quantitative approach, and the model chosen in this study is the Kurt Lewin model which consists of planning, action, observation, and reflection. This can be seen from the learning outcomes of students in cycle I obtaining a total score of 876 with an average score of 73 with a classical completeness percentage of 41.66% and cycle II obtaining a total score of 1092 with an average score of 91 with a classical completeness percentage of 100%. Thus it can be interpreted that by using the application of media images on parts of plants and their functions can improve student learning outcomes.